Influence of nano-additives on engine behaviour using diesel-biodiesel blend. (2022) - Devaraj, A.; Nagappan, M.; Yogaraj, D.; Prakash, Om; Rao, Y Anupam; Sharma, Abhishek
Abstract: Biodiesel, a potential liquid alternative fuel, offers an excellent property such as extend the longevity and clean burning fuel and reduces the greenhouse gas emissions since the trees planed for feedstock of biodiesel absorbs. It also helps to reduce dependency on fossil fuel and helps to economy. Biodiesel offers numerous advantages over conventional diesel, but it has some issues such as its high viscosity, poor cold flow properties, higher nitric oxide (NOx ) emissions and poor oxidation stability. Although there are many methods in order to overcome this drawback, addition of nanoparticles in biodiesel has emerged as one of the potential solutions. The nanoparticles improve the thermochemical properties of the fuel. Some studies have been carried out on nano-sized particles in diesel–biodiesel fuel emulsions. The current paper discusses about the effect of nano particles on engines performance and emission parameters and engine life. The paper also discusses about the effect of different size and dosage of nano particles on diesel engine behaviour. The preparation of nanofluid, several characterization methods and enhancing the stability of biodiesel via various techniques are also presented in this paper.